Digital Literacy Knowledge as an Intervening Variable Strengthens the Relationship between Perceived Ease and Usefulness and Intention to Use EMR at Koja Hospital - Wenny Ichwaniah; M. Natsir Nugroho; Erry Yudhya Mulyani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Digital transformation in the health sector is an urgent need, especially with the increasing demands for efficiency, accuracy, and security in managing medical information. This study aims to analyze the effect of perceived ease and perceived usefulness on the intention to use Electronic Medical Records (EMR) with digital literacy knowledge as an intervening variable in outpatient nurses at Koja Regional Hospital. The research method used is quantitative with a cross-sectional design. The sample consisted of 104 nurses selected using a purposive sampling technique. Data collection was carried out through a questionnaire using a 4-point Likert scale, covering the variables of perceived ease, perceived usefulness, digital literacy knowledge, and intention to use EMR. Data analysis was carried out using Lisrel software. Most of the subjects were female 82.7%, an average age of 41-50 years 40.4%, NERS education 52.9%, and work experience> 10 years 61.5%. Perceived ease and perceived usefulness have a positive and significant effect on the intention to use EMR. Digital literacy knowledge acts as an intervening variable that strengthens the relationship between perceived ease and usefulness on the intention to use. Thus, hospitals need to create a supportive work environment, by providing ongoing training and encouraging a collaborative culture in using new technologies in an effort to improve RME usage skills.